Consumers' attitudes of high-intensity ultrasound in Minas Frescal cheese processing: An innovative approach with text highlighting technique. (May 2023) - Scudino, Hugo; Tavares-Filho, Elson R.; Guimarães, Jonas T.; Mársico, Eliane T.; Silva, Marcia C.; Freitas, Mônica Q.; Pimentel, Tatiana C.; Esmerino, Erick A.; Cruz, Adriano G.
Graphical abstract: Abstract: Due to the intense competition in the sector, the dairy market maintains a constant search for innovations. Thus, new technologies are incorporated, and new products are constantly launched, increasing the range of consumer options. In this way, the understanding of consumers' motivations, attitudes, and behaviors in the moments of choice, purchase, and consumption are important for the academic public and food industries. This study used the Text Highlighting methodology to assess Brazilian consumers' explicit attitudes towards using high-intensity ultrasound technology in Minas Frescal cheese processing. In the task, consumers were asked to highlight in a text the terms they "liked" or "disliked" about using high-intensity ultrasound in the Minas Frescal cheese processing. A seven-point Likert scale was also used to assess consumers' attitudinal statements. A high engagement of consumers with the Text Highlighting methodology could be observed (43.8–92.3% of text highlighting), which suggests good intuitiveness of the technique. Including information about the benefits of the emerging technology in the product, mainly on sensory and nutritional properties, may increase positive consumer perception, as it promotes the consumers to express their value judgment in the form of "liked". At the same time, the harms of the traditional processing technique prompted consumers to express their value judgment in the "disliked" highlights. It was observed that information should be in a simple and direct language, as technical terminology in the text did not have a positive effect. The categorizing of consumers according to the sentimental score showed that consumers are still reticent to use emerging technologies in Minas Frescal cheese processing. Consumers' attitudinal statements demonstrated that consumers perceive high-intensity ultrasound as a positive idea and safety technology for Minas Frescal cheese processing. Still, they are not willing to pay premium prices. In conclusion, Text Highlighting produced valuable insights that can be used in communication strategies with Minas Frescal cheese consumers.